A aritmética escolar no ensino primário brasileiro: 1890-1946 - Costa, David Antonio da (2010)
This thesis analyzes the history of a school knowledge: the arithmetic in the Brazilian primary school. In specific, it discusses the transformations occurred with the teaching of the concept of number in the period 1890-1946. This temporal delimitation considers the time frame of the installation of school groups in Sao Paulo, going to the enactment of the Organic Law of Primary Education. The research takes as privileged sources the textbooks. The theoretical and methodological instrumental framework is rooted in cultural studies, in particular, in the field of History of School Subjects, described by André Chervel. The results of the study point to the changes with the arithmetic of primary education, and with the teaching of the concept of number, from the influences of Psychology in Education